Proprotein convertase 7 (PCSK7) reduces apoA‐V levels. (29th January 2020) - Ashraf, Yahya; Duval, Stéphanie; Sachan, Vatsal; Essalmani, Rachid; Susan‐Resiga, Delia; Roubtsova, Anna; Hamelin, Josée; Gerhardy, Stefan; Kirchhofer, Daniel; Tagliabracci, Vincent S.; Prat, Annik; Kiss, Robert Scott; et al.
Abstract : The locus of the human proprotein convertase subtilisin–kexin type‐7 (PC7) gene ( PCSK7 ) is on chromosome 11q23.3 close to the gene cluster APOA5/APOA4/APOC3/APOA1, a region implicated in the regulation of lipoprotein metabolism. A GWAS reported the association of PCSK7 SNPs with plasma triglyceride (TG), and exome sequencing of African Americans revealed the association of a low‐frequency coding variant of PC7 (R504H; SNP rs142953140 ) with a 30% TG reduction. Another PCSK7 SNP rs508487 is in linkage disequilibrium with a promoter variant of the liver‐derived apolipoprotein A‐V (apoA‐V), an indirect activator of the lipoprotein lipase (LpL), and is associated with elevated TG levels. We thus hypothesized that PC7 regulates the levels/activity of apoA‐V. Studies in the human hepatic cell line HuH7 revealed that wild‐type (WT) PC7 and its endoplasmic reticulum (ER)‐retained forms bind to and enhance the degradation of human apoA‐V in acidic lysosomes in a nonenzymatic fashion. PC7‐induced degradation of apoA‐V is inhibited by bafilomycin A1 and the alkalinizing agents: chloroquine and NH4 Cl. Thus, the PC7‐induced apoA‐V degradation implicates an ER‐lysosomal communication inhibited by bafilomycin A1. In vitro, the natural R504H mutant enhances PC7 Ser 505 phosphorylation at the structurally exposed Ser‐X‐Glu 507 motif recognized by the secretory kinase Fam20C. Co‐expression of the phosphomimetic PC7‐S505E with apoA‐V resulted in lower degradation compared to WT, suggesting that Ser 505 phosphorylation of PC7 lowers TG levels via reduced apoA‐V degradation. In agreement, in Pcsk7 −/− mice fed high‐fat diet, plasma apoA‐V levels and adipocyte LpL activity are increased, providing an in vivo mechanistic link for a role of liver PC7 in enhanced TG storage in adipocytes. Abstract : The PC7 gene ( PCSK7 ) is on chromosome 11q23.3 close to the gene cluster APOA5/APOA4/APOC3/APOA1, a region implicated in the regulation of lipoprotein metabolism. We propose that PC7 binds apoA‐V directly in the endoplasmic reticulum (ER) and the complex is then sorted to autophagosomes. These autophagosomes then fuse with lysosomes for degradation by macro‐autophagy, which is sensitive to bafilomycin A1.